(De)colonization runs deep: Mental health professionals working with Haitian migrants and activist mental health user and ex-user groups in Chile - Abarca-Brown, Gabriel; Montenegro, Cristian (Revista de Antropología Social, 2023)
In this article, we explore the epistemic, political, and ethical contradictions and conflicts that mental health practitioners embody in their work and interaction with Haitian migrants and activist service-user and ex-user groups in the public health system in Chile –marked by neoliberalization processes during the last thirty years. Based on two ethnographies, we argue that the work with both groups interrogates mental health practitioners regarding the scope of their disciplines and on a professional-individual level. Rather than passively reproducing discourses and practices of domination, practitioners embody contradictions and conflicts triggered by the incompatibility between “psy-disciplines”; the knowledge and practices anchored in Haitian-Creole medicine and Vodou; and the radical questioning of diagnoses and treatments developed by activist service-user and ex-user groups.  Practitioners question and challenge the universalist conceptions of identity, the mind, suffering, and treatment. Rather than an intellectual exercise, we emphasize that a call for decolonization implies the politicization of professional practice in –or outside– the borders of psychiatry and mental health as a system of government.
Keywords: decolonization; psy-disciplines; Haitian migration; activist service-user and ex user groups; Chile